Lessons Learned from 20 Years of Diabetes Self-Management Research With Mexican Americans in Starr County, Texas. (July 2014) - Brown, Sharon A.; Hanis, Craig L.
Purpose: The purpose is to provide an overview of a 20-year research program aimed at testing diabetes self-management education interventions culturally tailored for Mexican Americans residing in an impoverished rural community on the Texas-Mexico border. Methods: The research program involved focus group interviews to obtain community input, pilot testing to refine instruments and interventions, and community-based randomized controlled trials to examine intervention effects. Here the authors summarize lessons learned related to the (1) overall effects of culturally tailored diabetes self-management education; (2) impact of culture on study design, intervention development, health outcomes, and community acceptance; (3) benefits of and findings from multiple focus groups held over time in the community; and (4) personal and cultural motivators for behavioral change that were evident among study participants. Results: Postintervention reductions in A1C ranged from 1.4 to 1.7 percentage points. Individuals who attended ≥ 50% of intervention sessions achieved a 6–percentage point reduction in A1C. Intervention teams included bilingual Mexican American nurses, dietitians, and promotoras, all recruited from the local community. Focus group interviews indicated that a traditional promotora model was not acceptable to the participants who wanted knowledgeable health professionals, or perceived authority figures, to lead intervention sessions while promotoras provided logistical support. Free glucometers and strips, family participation, and interpersonal dynamics within intervention groups motivated individuals to make healthier lifestyle choices. Conclusions: Culturally tailored diabetes interventions are effective in improving the health of socially disadvantaged minorities who bear a disproportional burden of type 2 diabetes, and these interventions are cost-effective.